2013
DOI: 10.1101/cshperspect.a015560
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cells in Transplantation Rejection and Tolerance

Abstract: Mesenchymal stromal cells (MSCs) have recently emerged as promising candidates for cellbased immunotherapy in solid organ transplantation (SOT). In addition to immune modulation, MSCs possess proreparative properties and preclinical studies indicate that MSCs have the capacity to prolong graft survival and in some cases induce tolerance. Currently, the application of MSCs in SOT is being evaluated in phase I/II clinical trials. Whereas the mechanisms of action used by MSC immunomodulation have been somewhat el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 117 publications
(200 reference statements)
3
60
0
Order By: Relevance
“…Specifically, MSCs have been shown to decrease effector T cell response while promoting the emergence of regulatory T cells (Treg) [6]. These MSC properties suggest that they could be particularly attractive in solid organ transplantation (SOT) [7,8], and a consortium of European academic centres studying this subject has been created (http:// www.misot.eu). The first randomized controlled trial, evaluating the effects of autologous MSCs in living-related kidney transplantation has been performed in China [9].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, MSCs have been shown to decrease effector T cell response while promoting the emergence of regulatory T cells (Treg) [6]. These MSC properties suggest that they could be particularly attractive in solid organ transplantation (SOT) [7,8], and a consortium of European academic centres studying this subject has been created (http:// www.misot.eu). The first randomized controlled trial, evaluating the effects of autologous MSCs in living-related kidney transplantation has been performed in China [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, it does not have an ideal postoperative survival time because of immune rejection and islet toxicity of immunosuppressive agents [1,2]. The immunosuppressive effect and low immunogenicity of mesenchymal stem cells (MSCs) make them ideal candidates for immunosuppressive strategies [3,4]. Adult MSCs have been used widely in the allogeneic heart [5][6][7][8][9][10][11], liver [12], islet [13][14][15][16][17], kidney [18,19], and composite tissue transplants [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In association with moderate doses of certain immunosuppressive drugs, mesenchymal stem cells (MSCs) have shown unique immunoregulatory properties and promote long-term graft acceptance (17)(18)(19)(20). Various studies, including our own, have shown that MSC-mediated tolerance in vivo can be maintained by T reg cells (21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%